Introducing routine HIV screening for patients on an internal medicine residency inpatient service: a quality improvement project. Issue 1 (5th May 2016) - Padrnos, Leslie; Barr, Patrick; Klassen, Christine; Fields, Heather; Azadeh, Natalya; Mendoza, Neil; Saadiq, Rayya; Pauwels, Emanuel; King, Chris; Chung, Andy; Sakata, Kenneth; Blair, Janis
Abstract : The US Centers for Disease Control and Prevention (CDC) recommend human immunodeficiency virus (HIV) screening for all persons aged 13 to 64 years who present to a health care provider. We sought to improve adherence to the CDC guidelines on the Internal Medicine Resident Hospital Service. We surveyed residents about the CDC guidelines, sent email reminders, provided education, and engaged them in friendly competition. Credit for guideline adherence was awarded if an offer of HIV screening was documented at admission, if a screening test was performed, or if a notation in the resident sign out sheet indicated why screening was not performed. We examined HIV screening of a postintervention group of patients admitted between August 8, 2012, and June 30, 2013, and compared them to a preintervention group admitted between August 1, 2011, and June 30, 2012. Postintervention offers of HIV screening increased significantly (7.9% [44/559] vs 55.5% [300/541]; P<.001), as did documentation of residents' contemplation of screening (8.9% [50/559] vs 67.5% [365/541]; P<.001). A significantly higher proportion of HIV screening tests was ordered postintervention (7.7% [43/559] vs 44.4% [240/541]; P<.001). Monthly HIV screening documentation ranged from 0% (0/53) to 17% (9/53) preintervention, whereas it ranged from 30.6% (11/36) to 100% (62/62) postintervention. HIV screening adherence can be improved through resident education, friendly competition, and system reminders. Barriers to achieving sustained adherence to the CDC guidelines include a heterogeneous patient population and provider discomfort with the subject.